2013
DOI: 10.3171/2013.3.spine12420
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of superior cluneal nerve entrapment neuropathy

Abstract: Object Superior cluneal nerve (SCN) entrapment neuropathy is a poorly understood clinical entity that can produce low-back pain. The authors report a less-invasive surgical treatment for SCN entrapment neuropathy that can be performed with local anesthesia. Methods From November 2010 through November 2011, the authors performed surgery in 34 patients (age range 18–83 years; mean 64 years) with SCN entrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 10 publications
1
61
0
2
Order By: Relevance
“…Surgical release at the point where the SCN exits through the osteofibrous orifice has been reported as effective. 6,8,11 In some cases, intraoperative identification of the SCN is hampered by its thinness and its subcutaneous location after it penetrates through the orifice in an area with much fat tissue. We found that an incision placed at the trigger point and nerve stimulation under a microscope, while time-consuming, aids in the identification of the SCN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical release at the point where the SCN exits through the osteofibrous orifice has been reported as effective. 6,8,11 In some cases, intraoperative identification of the SCN is hampered by its thinness and its subcutaneous location after it penetrates through the orifice in an area with much fat tissue. We found that an incision placed at the trigger point and nerve stimulation under a microscope, while time-consuming, aids in the identification of the SCN.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] In fact, 1.6% 6 to 12% 4 of all LBP is due to SCN entrapment neuropathy. Surgical release at the point where the SCN exits through the osteofibrous orifice has been reported as effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, 14 we proposed criteria for the diagnosis of SCNEN. These include unilateral LBP involving the iliac crest and buttocks, a trigger point over the posterior iliac crest located 7 cm from the midline (corresponding to the nerve compression zone), and numbness and radiating pain in the SCN area upon compression of the trigger point ( Fig.…”
Section: Criteria For the Diagnosis Of Scnenmentioning
confidence: 99%
“…In patients with intermittent claudication, symptomatic improvement with spinal flexion, and evidence of spinal stenosis on imaging studies, LBP is considered to be due to LSS. [4][5][6] Superior cluneal nerve (SCN) entrapment neuropathy (SCNEN) is a cause of unilateral LBP involving the iliac crest and buttocks [1][2][3][12][13][14]16,18,20 that tends to be misdiagnosed as lumbar spine disorder. The clinical features and etiology of LBP remain poorly understood.…”
mentioning
confidence: 99%